Current status of liver transplantation in Latin America. (October 2020) - Contreras, Alan G.; McCormack, Lucas; Andraus, Wellington; de Souza M Fernandes, Eduardo; ,; Contreras, Alan G.; McCormack, Lucas; Andraus, Wellington; Fernandes, Eduardo de Souza M.; Requejo, Alejandro Serrablo; Jarufe, Nicolás; Dib, Martin; et al.
Abstract: The lack of adequate financial coverage, education, and the organization has been the main limiting factor for the development of transplantation in Latin America. As occurred worldwide, the number of patients on liver waiting lists in Latin America grows disproportionately compared to the number of liver transplantations (LTs) performed. Although many law modifications have been made in the last year, most countries lack social awareness about the importance of donation and the irreversibility of brain death. The mechanisms and norms for organ procurement and infrastructure development, capable of supporting this high demand, are still in slow progress in most countries. Access to LT in the region is very heterogeneous. While some countries have no active LT programs so far, others are an international model of a public transplantation system (Brazil) or a national information system (Argentina). While some countries have only a few LT centers, others have too many LT centers performing an inadequate low number of LTs. Disparity to access transplantation remains the major challenge in the region. Cultural and educational efforts have to be accompanied by transparent public policies that will likely increase organ donation and activity in transplantation. The purpose of this article is to review the trends and current activity in LT within Latin America, based on prior publications and the information available in each country of the region. Highlights: Organ donation and Liver transplantation activity in Latin America is very heterogeneous. Disparity to access to transplantation remain the major challenge in the region. LT is not performed in 7 countries: Guatemala, Trinidad y Tobago, Honduras, Nicaragua, Panama, El Salvador, and Haiti. Some active countries have only few LT centers, others have too many LT centers performing an inadequate low number of LTs. There is still a lag in the evolution of public policies regarding organ allocation and transplantation. Some countries have center-based allocation system whereas most have moved toward recipient-based system. LT should be limited to centers with financial support on a legal framework that favors equality and justice for the patients.